(untitled) (Stamford Journal of Microbiology, 2025)
Dengue, the most dominant mosquito-borne infectious disease of humans that recurring global health problem. In Bangladesh, dengue outbreaks are on the increase despite the efforts of the government, and it is not clear what the understanding of the general Dhaka population towards dengue fever is. This study aims to assess the prevalence of dengue virus infection among suspected cases through laboratory-based molecular methods. Here, 93 samples from suspected patients at different diagnostic centers in Dhaka City, Bangladesh, were reported. Suspected samples were analyzed by the RT-PCR technique. Of the 93 samples tested, 20.43% were positive for dengue virus, while 79.57% were negative. It was observed that among various age major number of positive cases were male compared to females. In addition, the most affected age group was 41–60 years (63.16%), followed by 21–40 years (31.58%), while only 5.26% of cases were observed in individuals aged 18 years or below. This pattern may reflect a male predominance over females, increased outdoor activity, or occupational exposure among adults, particularly middle-aged groups, which could contribute to a higher infection risk. These findings highlight the importance of RT-PCR based accurate detection of dengue as well as awareness and prevention strategies, especially for high-risk demographic groups. Stam. J. Microbiol. 2025;15(1):17-20